Missing link the evolution of metaphor and the metaphor of evolution - Donaldson, Jeffery, 1960- (desLibris. Books collection., 2015)
We look for missing links in the sciences and humanities, but the essential missing link - metaphor - is always in front of us. In Missing Link, Jeffery Donaldson unites literary criticism and evolutionary and cognitive science to show how metaphor has been with us since the beginning of time as a seed in the nature of things. With examples from centuries of poets, critics, philosophers, and scientists, he details how metaphor is a chemistry, an exchange of energies forming and dissolving, and an openness in the spaces between things. He considers the ways in which DNA learns how to liken things that have been, how mutation makes errors and then tries them on, and how evolution is hypothesis - nature's way of "thinking more." The mind is a matrix of relations: neural synapses cascade into ever-changing pathways and patterns. Metaphor is the substance of things hoped for, the evidence of things not seen. It is the unbroken thread between matter and spirit. Whether offering analysis of a turn of phrase or chemical reaction, Missing Link presents a vision of literature that is also a vision of the cosmos, and vice versa. It enters the debate between evolution and religion, and challenges scientists, literary theorists, and religious advocates to rethink the relations between their disciplines.